STUDI PERBANDINGAN PERKAWINAN ANAK DALAM HUKUM ADAT DI INDONESIA DAN INDIA DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Yunita Syofyan; Didi Nazmi (UNES Journal of Swara Justisia, 2023)
The Convention on the Rights of the Child (Convention of the Rights of the Child) defines a child as every human being under the age of 18 (eighteen) years so that marriage (marriage) carried out by someone who has not reached the age of 18 is internationally categorized as Child marriage is also a form of violence against children and is a violation of human rights. The patterns and diversity of forms of marriage found in each region make Indonesia rich in culture, however, if one pays attention to the forms of marriage in Bulukumba Regency, especially in Ara Village, which is one of the regions in Indonesia, forms of marriage still violate positive law. . Where in this area there are still child marriages for reasons of local customs. Apart from this area, it also occurs in the Dayak tribe, Kalimantan. Several countries in the world still exist due to customs that marry children, including Pakistan, Africa and India. Child marriage can only be understood when examined from the point of view of the dynamics between state law, religious law and customary law. The legal culture of society and the role of religious leaders are important factors in determining the acceptance or rejection of child marriage.